THE CHEMICAL COMPOSITION OF VANNAMEI SHRIMP(Litopenaeus vannamei)SKINAND HEAD FLOUR - Anisa Anastasia Yunus; Mirna Ilza; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT            Vannameishrimp are used frequently by people, whether whole vannamei shrimp or without the skinand head. So that unused skin and head waste can pollute the environment. Unused skin and head waste have nutritional value so that they can still be reused. This study aims to determine the proportion value and chemical composition of the skin and head flour ofshrimp vannamei. The researchmethod consisted of two stages, namely: 1) Preparation of skin and head flour waste of vannamei shrimp, 2) Chemical analysis of skin and head flour waste of vannamei shrimp. The parameters observed consisted of morphology, vannameishrimp proportion, and chemical composition of skin and head flour of vannamei shrimp.The results showed that vannamei shrimp measuring 13 cm had a proportion value of 16.67% head, 13.33% skin, and 56.67% meat. The chemical composition of the skinand head flour of vannamei shrimp containedwater, ash, protein, fat, and carbohydrate was 10.20% (WW), 33.46% (DW), 38.62% (DW), 1.65% (DW), and 26.27% (DW), respectively.Keywords: Vanname shrimp, Carapace, Morphology, Proximate, Proportion